Volume 6: Turbomachinery, Parts A, B, and C 2008
DOI: 10.1115/gt2008-50260
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Unsteadiness on the Performance of a Transonic Centrifugal Compressor Stage

Abstract: Numerical and experimental investigations were conducted in a transonic centrifugal compressor stage composed of a backswept splittered unshrouded impeller and a vaned diffuser. The characteristic curves of the compressor stage resulting from the unsteady simulations and the experiments show a good agreement over the whole operating range. On the contrary, the total pressure ratio resulting from the steady simulations is clearly overestimated. A detailed analysis of the flow field at design operating point led… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 0 publications
3
18
0
Order By: Relevance
“…As already observed in a previous work [10], a better correspondence is obtained between experiment and unsteady simulations compared to the stationary ones. In particular, the steady-state computations overvalue the blockage massflow and the pressure ratio of the compressor stage.…”
Section: Overall Performancesupporting
confidence: 87%
See 1 more Smart Citation
“…As already observed in a previous work [10], a better correspondence is obtained between experiment and unsteady simulations compared to the stationary ones. In particular, the steady-state computations overvalue the blockage massflow and the pressure ratio of the compressor stage.…”
Section: Overall Performancesupporting
confidence: 87%
“…This code solves the compressible RANS equations by a cell-centered finite volume method. The turbulence model chosen for this study is the two-equation model of Smith (k-l), that was shown by Rochuon [9] and Trébinjac et al [10] to provide results in a good accordance with the experiments in the case of a transonic centrifugal compressor stage. Both steady-state and unsteady numerical computations were performed.…”
Section: Numerical Proceduresmentioning
confidence: 99%
“…In this machine, the surge is thought to initiate in the diffuser passages. Indeed it has been shown [3] that the diffuser was the most sensitive component to unsteadiness which came from two sources: the jet-wake structure (emanating from the impeller flow) and the interaction between the diffuser vane bow shock wave and the impeller blade pressure surface leading to pressure waves which propagate in the diffuser passages.…”
Section: Test Rigmentioning
confidence: 99%
“…The global shape and the amplitude of the fluctuations are consistent and help to show the reliability of the results. Refer to [3] for more information about the URANS calculation. Fig.…”
Section: Processing Of the Raw Datamentioning
confidence: 99%
“…[7][8][9][10]. It is generally agreed that the effects of this unsteady flow on diffuser performance are limited at design conditions.…”
Section: Introductionmentioning
confidence: 99%